Chemical modification of polymer surfaces for advanced triboelectric nanogenerator development. (December 2016) - Yu, Yanhao; Wang, Xudong
Abstract: Triboelectric nanogenerator (TENG) is a newly developed technique for harvesting mechanical energy from ambient environment with sparkly high output and extremely flexible structural designs. The operation of TENGs is based on the combined effects of triboelectrification and electrostatic induction. The charge density on triboelectric surfaces (mostly polymers) sets the foundation of TENG output. Meanwhile, the charge density on polymer surface is closely related to the surface chemical property. Therefore, engineering the surface chemical environment by appropriate functionalization is the most fundamental approach in controlling the TENG outputs. This article systematically reviews recent processes of chemical modifications of triboelectric polymers for advanced TENG developments. According to different functionalization techniques, four categories of chemical modifications, including fluorinated surface, ion injection, sequential infiltration synthesis and molecular-targeting functionalization are thoroughly reviewed, and their contributions to TENG performance are discussed.